Electrophoresis of a Cylinder in a Cylindrical Tube (Communications in Computational Physics, 2017)
Electrophoresis of a cylinder suspended in a cylindrical tube is analyticallystudied in the limit of thin electric double layer approximation. The electric and fluidflow fields within the annulus, and the cylinder velocities are analytically obtained inbipolar coordinates. The results are analyzed with various values of dimensionless parameters:eccentricity, cylinder-to-tube radius ratio and tube-to-cylinder zeta potentialratio (i.e., tube-to-cylinder velocity scale ratio). The analysis shows that microvorticesare generated within the annulus. By changing the parameters, different flow patternscan be created, which shows potential for mixing enhancement in micro/nanofluidics.Moreover, the cylinder not only translates but also rotates when the cylinder and tubeare eccentric. The cylinder rotation might be utilized as a micromotor or an electricfield detector. The cylinder trajectories show that the cylinder may approach the tubewall or rest within the tube depending on the zeta potential ratio.